Phase I study of imatinib, cisplatin and 5-fluoruracil or capecitabine in advanced esophageal and gastric adenocarcinoma - Mayr Martina; Becker Karen; Schulte Nadine; Belle Sebastian; Hofheinz Ralf; Krause Annekatrin; Schmid Roland M; Röcken Christoph; Ebert Matthias P (BMC Cancer, 2012)
Abstract Background Despite all benefit provided by established therapies prognosis of gastric cancer remains poor. Targeted inhibition of platelet derived growth factor receptor (PDGFR) by imatinib may influence tumor growth and amplify chemotherapeutic effects. Methods This phase I study evaluated dose limiting toxicity (DLT) of imatinib combinated with chemotherapy according to a 3-patient cohort dose-escalating design. Thirty-five patients received cisplatin (60 mg/m2 d1 q 3w)/ capecitabine (1250 mg/m2 bid d1-14 q 21) or cisplatin (50 mg/m2 d1 q 2w)/ 5-fluoruracil (2 g/m2 d1, q 1w). Imatinib was started d - 4 with dose escalation from 300 to 700 mg QD in 100 mg steps. Results At imatinib dose level 1 (300mg) one DLT was observed, three more patients were enrolled without further DLT. At dose level 5 (700 mg) two gastric perforations occurred, so 600 mg imatinib emerged as the maximum tolerated dose. Major grade 3/4 toxicities were nausea (6%), anemia (6%) and fatigue (3%). Response evaluation revealed partial response in 27% and stable disease in 43% of the assessable patients. Conclusions Combination of imatinib and chemotherapy is well tolerated. Response rates were not superior to those of standard therapy. Further investigations of a larger group of patients are required to confirm the amplification of chemotherapy effects by imatinib. Trial registration European Clinical Trials Database: Eudra-CT2006-005792-17 and Clinical Trials Database: NCT00601510